2020
DOI: 10.1038/s41598-020-77680-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection on sleep duration in Drosophila melanogaster

Abstract: Sleep is ubiquitous across animal species, but why it persists is not well understood. Here we observe natural selection act on Drosophila sleep by relaxing bi-directional artificial selection for extreme sleep duration for 62 generations. When artificial selection was suspended, sleep increased in populations previously selected for short sleep. Likewise, sleep decreased in populations previously selected for long sleep when artificial selection was relaxed. We measured the corresponding changes in the allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…with increases in the population frequency of the 'G' allele with increasing sleep, while the frequency of the 'A' allele increased with decreasing sleep. When the selective breeding procedure was relaxed, the frequency of the 'G' allele increased in short-sleeping populations, paralleling an increase in sleep [100]. One possibility is that this polymorphism contributes to the changes in gene expression in ringer that we observed in the present study.…”
Section: Plos Computational Biologymentioning
confidence: 53%
“…with increases in the population frequency of the 'G' allele with increasing sleep, while the frequency of the 'A' allele increased with decreasing sleep. When the selective breeding procedure was relaxed, the frequency of the 'G' allele increased in short-sleeping populations, paralleling an increase in sleep [100]. One possibility is that this polymorphism contributes to the changes in gene expression in ringer that we observed in the present study.…”
Section: Plos Computational Biologymentioning
confidence: 53%
“…First, standing genetic variation for sleep and activity traits in the DGRP is much lower than would be expected compared to a neutrally evolving model, suggesting that stabilizing selection acts against de novo mutations to favor intermediate phenotypes over extremes 46 . Similarly, a selective breeding experiment demonstrated that natural selection acts against extreme long and short sleep duration, shifting the allele frequencies of genomic modifiers to generate more moderate sleep 47 . In addition, long-standing stocks of Shaker mutant alleles did not exhibit a short-sleeping phenotype until outcrossed, suggesting that accumulated de novo mutations suppressed the expected short sleep duration phenotype 48 .…”
Section: Discussionmentioning
confidence: 99%
“…In that study we identified a polymorphism in an intron of ringer that changed in allele frequency with selection, with increases in the population frequency of the ‘G’ allele with increasing sleep, while the frequency of the ‘A’ allele increased with decreasing sleep. When the selective breeding procedure was relaxed, the frequency of the ‘G’ allele increased in short-sleeping populations, paralleling an increase in sleep ( Souto-Maior et al, 2020 ). One possibility is that this polymorphism contributes to the changes in gene expression in ringer that we observed in the present study.…”
Section: Discussionmentioning
confidence: 99%